2004
DOI: 10.1098/rsta.2004.1437
|View full text |Cite
|
Sign up to set email alerts
|

Applications of carbon nanotubes in the twenty–first century

Abstract: Carbon nanotubes, which consist of rolled graphene sheets built from sp(2) hybridized carbon atoms, are now attracting scientists from various disciplines due to their fascinating physico-chemical properties. In this account, we will review the recent progress on the synthetic techniques for the large-scale production of carbon nanotubes, especially focusing on the floating-catalyst method used in the chemical vapour deposition (CVD) process. We will also describe effective purification methods avoiding struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(96 citation statements)
references
References 62 publications
0
92
0
4
Order By: Relevance
“…They exhibit unusual strength and unique electrical properties and are extremely efficient conductors of heat. 1 Studies reported on carbon nanotubes to date have suggested their utility in a large number of sectors from microdevices and electronics to biological applications. The use of carbon nanotubes in various biological applications raises questions regarding the safety of its use and urges vigorous toxicological evaluations in various models.…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit unusual strength and unique electrical properties and are extremely efficient conductors of heat. 1 Studies reported on carbon nanotubes to date have suggested their utility in a large number of sectors from microdevices and electronics to biological applications. The use of carbon nanotubes in various biological applications raises questions regarding the safety of its use and urges vigorous toxicological evaluations in various models.…”
Section: Introductionmentioning
confidence: 99%
“…4 These unique properties render CNTs suitable for application in various fields for example, their use as supports in catalysis, nanoconveyors, field emission sources, chemical sensors, nanoelectronic devices and in fuel cells. 5,6 Methods for making CNTs such as arc discharge, laser ablation, pyrolysis and catalytic chemical vapour deposition (CCVD) have been developed. [7][8][9][10] To date the production of CNTs by the CCVD method remains the preferred route for their large scale production.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have emerged as suitable alternatives to overcome the limitations of conventional micro composites [2]. The carbon nanotubes (CNTs) are a promising raw material for industrial applications due to their outstanding properties [3]. Their application in conductive high strength composites [4] and interconnects [5] have received worldwide attention and interest.…”
Section: Introductionmentioning
confidence: 99%